2016
DOI: 10.1002/anie.201603648
|View full text |Cite
|
Sign up to set email alerts
|

A Single Methylene Group in Oligoalkylamine‐Based Cationic Polymers and Lipids Promotes Enhanced mRNA Delivery

Abstract: The development of chemically modified mRNA holds great promise as a new class of biologic therapeutics. However, the intracellular delivery and endosomal escape of mRNA encapsulated in nanoparticles has not been systematically investigated. Here, we synthesized a diverse set of cationic polymers and lipids from a series of oligoalkylamines and subsequently characterized their mRNA delivery capability. Notably, a structure with an alternating alkyl chain length between amines showed the highest transfection ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 17 publications
0
63
1
Order By: Relevance
“…This stands in stark contrast to previous studies on intravenous delivery of PBAE‐DNA complexes, in which jetPEI outperformed PBAEs by two orders of magnitude in the lungs . A recent study demonstrated in vivo mRNA expression in the lungs after pulmonary administration of cationic polymeric nanoparticles; however, to our knowledge, ours is the first example of biodegradable polymeric nanoparticles successfully delivering mRNA to the lungs after intravenous injection in mice.…”
Section: Figurecontrasting
confidence: 95%
See 1 more Smart Citation
“…This stands in stark contrast to previous studies on intravenous delivery of PBAE‐DNA complexes, in which jetPEI outperformed PBAEs by two orders of magnitude in the lungs . A recent study demonstrated in vivo mRNA expression in the lungs after pulmonary administration of cationic polymeric nanoparticles; however, to our knowledge, ours is the first example of biodegradable polymeric nanoparticles successfully delivering mRNA to the lungs after intravenous injection in mice.…”
Section: Figurecontrasting
confidence: 95%
“…The function of PEGylated DD90‐C12‐122 and C32‐C12‐118 nanoparticles demonstrated here warrants continued development and optimization to further improve potency. One approach to potentially access even more potent formulations would utilize design‐of‐experiments methodology to vary the formulation components, which has been shown to improve mRNA delivery efficacy in a separate liver‐targeting system . Importantly, these data demonstrate a correlation between serum stability and in vivo efficacy; the terpolymers that form serum‐stable nanoparticles when formulated with a low amount (7 mol %) of PEG‐lipid also led to the most potent in vivo mRNA delivery.…”
Section: Figurementioning
confidence: 99%
“…For in vivo purposes, cmRNAs (AA and AAstop) were formulated using Ethris’ (Planegg, Germany) proprietary cationic lipid formulation LF132, which was based on Jarzebińska et al. 57 In order to examine their effectiveness in vitro , cells were transfected with 10, 50, and 100 ng/100 μL of AA-LF132 or AAstop-LF132. As vehicle control, 2% sucrose (diluted accordingly) was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Oligoalkylamines grafted to an 8000 Da poly(acrylic acid) (PAA8k) scaffold complexed with chemically modified mRNA resulted in another kind of polyplexes with transfection capacity. Intravenous administration of PAA8k-luciferase mRNA systems in mice showed different luminescence signal in liver depending on their structure [125].…”
Section: Polymeric Systemsmentioning
confidence: 99%